1999
DOI: 10.3354/meps188179
|View full text |Cite
|
Sign up to set email alerts
|

The cause and consequence of ontogenetic changes in social aggregation in New Zealand spiny lobsters

Abstract: Ontogenetic changes in the behavior, spatial distribution, or habitat use of a species are presumably adaptations to ecological forces that dlffer in their effect on various life stages. The New Zealand rock lobster Jasus edwardsii is one of several species of spiny lobster that exhibits dramatic ontogenetic shifts in sociality and spatia.1 distribution, and we tested whether such changes are adaptive. We first surveyed several natural populations of J. edwardsii to document size-speclfic differences in aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…The authors indicated that pods could vary in form and structure depending on the species, time of year, and area where the pods formed, as well as the characteristics of the individuals that form them (maturity stage, intermoult stage). A protective function has also been suggested for juvenile aggregations of spiny lobsters (Eggleston et al, 1990;Smith & Herrnkind, 1992;Butler et al, 1999).…”
mentioning
confidence: 99%
“…The authors indicated that pods could vary in form and structure depending on the species, time of year, and area where the pods formed, as well as the characteristics of the individuals that form them (maturity stage, intermoult stage). A protective function has also been suggested for juvenile aggregations of spiny lobsters (Eggleston et al, 1990;Smith & Herrnkind, 1992;Butler et al, 1999).…”
mentioning
confidence: 99%
“…In contrast, there is no evidence that spiny lobsters use olfactory cues to detect and avoid piscine predators (Schratwieser 1999), nor would flight or multiple den entrances seem a particularly valuable strategy for evading fastswimming fish predators. Instead, group defense by spiny lobster is a well-documented and effective means of reducing piscine predation (Mintz et al 1994, Eggleston et al 1997, Butler et al 1999 , and our results demonstrate that it is also effective against octopuses. Alternatively, multiple lobsters fleeing an octopus predator in a confined space may have lessened predation due to a confusion effect on the octopus (Neill & Cullen 1974).…”
Section: Discussionmentioning
confidence: 68%
“…Aggregation with conspecifics increases the survival of lobsters subject to predation (Smith & Herrnkind 1992, Mintz et al 1994, Butler et al 1999, Dolan & Butler 2006; therefore, we also investigated whether the presence of octopuses on a site effected the local pattern of lobster aggregation in artificial shelters. First, we calculated a standardized Morisita's index of dispersion (I δ ) for each site to determine if the lobsters present were evenly distributed (I δ < 0), randomly distributed (I δ = 0), or clumped (I δ > 0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesized functional benefits of den sharing include the dilution effect or group defence against predators (Eggleston and Lipcius 1992, Mintz et al 1994, Butler et al 1999), the guide effect, which reduces predation risk during the search for shelter (Childress and Herrnkind 2001), and cohabitation of smaller more vulnerable juveniles with larger conspecifics that have greater defensive abilities (Sosa-Cordero et al 1998, Briones-Fourzán et al 2007.…”
Section: Introductionmentioning
confidence: 99%